Anestezija pri endoskopskih bariatričnih operacijah - Požar-Lukanovič, Neva (Endoskopska revija, 2007)
The increasing incidence of morbid obesity in Western society has led to a growing number of extremely obese patients presenting for surgical treatement.Morbid obesity and coexistent conditions put these individuals at increased risk for anaesthesia-related complications. Pneumoperitoneum during bariatric surgery may worsen some specific pathophysiological properties of the morbidly obese. Difficult airway, changed reaction to anaesthetics, and prolonged and complicated recovery from anaesthesia are also of special concern. However, the rate of these complications has decreased recently as a result of increased experience with bariatric surgery for morbid obesity.
Keywords: Anestezija inhalacijska; Obesity, Morbid; Surgery; Debelost bolezenska; Laparoscopy; Laparoskopija; endoskopska kirurgija; Anesthesia, Inhalation; debelost; bariatrična kirurgija; anestezija